United Nations Manual for the Negotiation of Bilateral Tax Treaties between Developed and Developing Countries - United Nations Department of Economic; Social Affairs (United Nations, 2016)
The Manual for the Negotiation of Bilateral Tax Treaties between Developed and Developing Countries provides a guide to all aspects of tax treaty negotiation, including a brief description of the Articles of the United Nations Model Double Taxation Convention between Developed and Developing Countries. It is intended mainly for negotiators with little or no experience in the negotiation of tax treaties.